Post-operative analgesia for shoulder arthroscopic surgeries: A comparison between inter-scalene block and shoulder block - Pani, Nibedita (Indian J Anaesth, 2019)
BACKGROUND AND AIMS: Shoulder arthroscopic surgeries can produce intense post-operative pain. Inter-scalene block (ISB) provides good analgesia after shoulder surgery, but concerns over its associated risks have prompted the search for alternatives. Shoulder block (SHB), which includes suprascapular block along with axillary nerve (AN) block, was recently proposed as an alternative to ISB, but evidence of its efficacy is conflicting. The aim of our study was to compare SHB with ISB in shoulder surgery for post-operative analgesia. METHODS: A total of 76 patients scheduled for shoulder arthroscopic surgery were equally divided into 2 groups of 38 patients each: ISB group and SHB group. Both the nerve blocks were achieved by using ultrasound and a nerve stimulator. Visual analogue scale (VAS) scores were evaluated at 1, 4, 6, 12 and 24 h post-operatively. The time to first analgesia request, total analgesic requirement for 24 h post-operatively, patient satisfaction and any complications were recorded. RESULTS: SHB provided equivalent analgesia to ISB in terms of post-operative VAS scores. Time to first analgesic request was 6.2 ± 1.3 h in ISB group and 5.9 ± 1.2 h in SHB group, which was not statistically significant. Complications like subjective dyspnoea and weakness of arm were significantly higher in ISB group compared to SHB group. Patient satisfaction scores were also significantly higher in SHB group compared to ISB group. CONCLUSION: SHB is as effective as ISB for post-operative pain relief and with fewer complications due to selective blockade of suprascapular and axillary nerves.